The Influence of Financial Technology and Financial Security on Interest in Using Financial Technology (Study of Accounting Students at Muhammadiyah University of Makassar) - Alif Ridhotullah Ichsan; Muchriana Muchran; Hasanuddin (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the influence of financial technology and financial security on interest in using financial technology (study of accounting students at Muhammadiyah University, Makassar). The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. The population in this research is accounting students class of 2020 at Muhammadiyah University, Makassar. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 22 application regarding the influence of financial technology and financial security on interest in using financial technology (study of accounting students at Muhammadiyah University of Makassar) which has been discussed in the previous chapter, So the author can conclude that financial technology has a positive and significant effect on students' interest in using financial technology and financial security has a positive and significant effect on students' interest in using financial technology..